Characterization of the catalytic mechanisms of two aminoglycoside phosphotransferases: APH(3')-IIIa from Enterococcus faecalis and APH(9)-Ia from Legionella pneumophila - Thompson, Paul R. (My University, 1999)
While the aminoglycoside antibiotics continue to be useful chemotherapeutic agents, the appearance and dissemination of high level aminoglycoside resistant strains is a threat to the future clinical relevance of these antibiotics. Since there are only a limited number of alternative antibiotics, and resistance to all of these therapies has been observed, there is an urgent need to either introduce new classes of antibiotics or to 'rehabilitate' the ones currently employed. The development of drugs that inhibit the resistance mechanism is one method to 'rehabilitate' the usefulness of these antibiotics. As such, we are employing structure based drug design techniques for the development of inhibitors to several enzymatic aminoglycoside resistance mechanisms. A prerequisite for this method of drug design is a thorough knowledge of the catalytic mechanism of the enzyme, and as such I have characterized the regiospecificity and phosphoryl transfer mechanism of two aminoglycoside phosphotransferases: APH(3' )-IIIa and APH(9)-1a. From these studies, described herein, it is now known that the APH(3' )-IIIa enzyme catalyzes the direct transfer of the γ-phosphate of ATP to either the 3' -hydroxyl of 4,6-disubstituted aminoglycosides, or the 3' - and 5'' -hydroxyl of 4,5-disubstituted aminoglycosides, providing that both hydroxyl groups are present. It is also now known that APH(9)-la catalyzes the transfer of the γ-phosphate of ATP to the 9-hydroxyl of spectinomycin. Site directed mutagenesis, kinetic, metal, solvent isotope, and solvent viscosity studies of these two enzymes indicate that a dissociative-like transition state is employed, and that phosphate transfer occurs through a biomechanical process.
Keywords: Biochemistry; Biochemistry